Illegal migration from Bangladesh - Kumar, B. B. (ed.) (New Delhi, 2006)
This compendium of twenty-three papers, presented at a national seminar, organised by Astha Bharati, Delhi, in association with the Centre for North East Studies and Policy Research, addresses a wide range of issues concerning the complex problem of illegal migration from Bangladesh. Tracing the factors responsible for illegal migration, both historical and politico-economic, the contributors analyse its implications for India in general and the North Eastern states in particular-pushing high Population growth, disturbing the demographic texture of population, threatening internal security, deteriorating Economy and influencing electoral politics.
Keywords: India-Emigration and immigration